Are Economic Growth, Institutional Quality and Natural Resources necessities for Human Development? Empirical Evidence from selected West African Economies - Hosu, Yiseyon Sunday; Matsvai, Simion (International Journal of Economics and Financial Issues, 2025)
The impact of institutions and natural resources on economic growth have been examined by several researchers with little attention being paid on the impact of such variables on human capital development. Premised on the Sustainable Development Goals that targets sustained and inclusive growth and development measured in both macro and per capita terms, the study seeks to examine the impact of economic growth, institutional quality and natural resources on human development in 14 West African countries for the period from 2010 to 2021. Panel data estimation techniques were used in this study. Due to many economic variables (human Capital development and human development index) being dynamic, Arellano-Bond’s (GMM) dynamic panel-data analysis was justified and most appropriate. The dependent variable that is Human development was measured in two (human capital development and human development index) and hence two models under each were estimated. Results revealed that the lagged values of both human capital development index and human development index affect human capital development in west Africa positively. A negative and statistically significant relationship with human development (human capital index and human development index) was revealed on income from natural resources and real gross domestic product. Institutional variables like corruption control, political stability and government effectiveness were found to have positive and statistically significant relationships with human development indicators used in the study. By ensuring equitable distribution on wealth and natural resources rents, and enhancing institutional quality, human capital development in West African economies can be realised and sustainable development goals can be achieved. Governments should continue to control corruption, ensure political stability and government effectiveness.